2011
DOI: 10.1105/tpc.111.083089
|View full text |Cite
|
Sign up to set email alerts
|

The Jasmonate-ZIM Domain Proteins Interact with the R2R3-MYB Transcription Factors MYB21 and MYB24 to Affect Jasmonate-Regulated Stamen Development in Arabidopsis    

Abstract: The Arabidopsis thaliana F-box protein CORONATINE INSENSITIVE1 (COI1) perceives jasmonate (JA) signals and subsequently targets the Jasmonate-ZIM domain proteins (JAZs) for degradation by the SCF COI1 -26S proteasome pathway to mediate various jasmonate-regulated processes, including fertility, root growth, anthocyanin accumulation, senescence, and defense. In this study, we screened JAZ-interacting proteins from an Arabidopsis cDNA library in the yeast two-hybrid system. MYB21 and MYB24, two R2R3-MYB transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
475
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 529 publications
(489 citation statements)
references
References 82 publications
(121 reference statements)
14
475
0
Order By: Relevance
“…However, new insights have recently emerged on the regulatory mechanisms of JA signaling, including identification of JAZ binding partners, and the influence of circadian rhythms and hormonal crosstalk (Hou et al, 2010;Qi et al, 2011;Song et al, 2011;Goodspeed et al, 2012;Hong et al, 2012;Shin et al, 2012;Yang et al, 2012). These suggest that JA signaling encompasses multiple complicated regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, new insights have recently emerged on the regulatory mechanisms of JA signaling, including identification of JAZ binding partners, and the influence of circadian rhythms and hormonal crosstalk (Hou et al, 2010;Qi et al, 2011;Song et al, 2011;Goodspeed et al, 2012;Hong et al, 2012;Shin et al, 2012;Yang et al, 2012). These suggest that JA signaling encompasses multiple complicated regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Expression analysis of the six TaMYB genes indicated that they were expressed in root, sheath and leaf, but at different abundance. Another study by Song et al (2011) demonstrated that the R2R3-MYB transcription factors MYB21 and MYB24 function as direct targets of JAZs to regulate male fertility specifically. They speculated that JAZs interact with MYB21 and MYB24 to attenuate their transcriptional function; upon perception of JA signal, COI1 recruits JAZs to the SCF COI1 complex for ubiquitination and degradation through the 26S proteasome.…”
Section: Hormone Responsesmentioning
confidence: 99%
“…These MYC TFs interact with most of the 12 JAZ proteins and act redundantly to regulate diverse aspects of JA responses, including root growth inhibition and defense gene expression Fernández-Calvo et al, 2011;Kazan and Manners, 2013;Schweizer et al, 2013). In addition to these MYC proteins, recent studies have identified numerous TFs that interact with JAZ proteins and regulate different aspects of JAdependent transcriptional responses Song et al, 2011;Zhu et al, 2011;Hu et al, 2013;Jiang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%